The practice of bond breaker application in concrete tilt-up construction - Moran-Puentes, Eduardo (Kansas State University, 2019)
As concrete tilt-up construction continues to grow both nationally and internationally, accompanying this growth is the use and application of bond breakers. A bond breaker is a material that is used to prevent adhesion of newly placed concrete to the substrate, it is available in several forms including liquid, tape, and spray. Perhaps no other chemically manufactured product is more poorly understood or misused as bond breakers. The following report examines the current practice of bond breaker application in concrete tilt-up construction in the United States through an anonymous electronic questionnaire survey. The survey sought to evaluate the level of communication and knowledge for proper application of bond breakers between industry professionals across this sector of the concrete industry. The survey sought to identify potential barriers and miscommunications in their procedures of bond breaker application. Comparing the survey’s results to the manufacturers application recommendations revealed an industry wide inconsistency of bond breaker application and weather considerations affecting the application procedure. This study aims to bring awareness and to bridge the gap of inconsistent practices involving bond breaker application by determining the sources of miscommunication that could cause the misuse of these products.
Keywords: Tilt-up construction; Bond breaker; Application; Tilt-wall construction